Enhancing Filter Assembly and Printing Efficiency through Automation and Virtual Reality Integration - Malega, Peter; Daneshjo, Naqib; Kovac, Juraj; Korba, Peter (Engineering, Technology & Applied Science Research, 2024)
This paper presents a comprehensive approach to improving the assembly and printing process of filters in a selected company. Currently, the company's process involves significant manual labor, which leads to inefficiencies and potential health risks for employees. The proposed solution integrates the use of pneumatic cylinders to automate the assembly and printing process, reducing manual effort and improving production efficiency. The fixture and filter were modeled using SOLIDWORKS 2022 and simulated in virtual reality with Pixyz Review software. The virtual reality simulation serves as an innovative training tool for new employees, enhancing understanding and accuracy in the assembly process. The study compares the current state, where manual handling results in a time-consuming process with a lower production rate, to the proposed automated system. The proposed solution eliminates unnecessary intermediate storage and manual fixture transfers, significantly reducing the total assembly and printing time from 24 s to 22 s per unit. This results in a 14.16 % increase in production efficiency, allowing the company to produce 1227.3 filters per shift compared to the current 1075 filters.